Multiple sclerosis fatigue and relationship to depression and physical disability - (:unkn) unknown (My University, 2001)
Objective: Fatigue is a frequent and often disabling symptom in multiple sclerosis. The association of fatigue with physical disability is poor, as it is not the whole cause of fatigue. Recently, depression has been reported as a predictor of multiple sclerosis fatigue. Methods: In order to investigate the association between fatigue, depression and disability, 18 relapsing and remitting multiple sclerosis patients were administered the fatigue descriptive scale and Hamilton depression scale during a regular out-patient visit. Results: Fatigue was present in 77.7 % of the patients and described as asthenia (fatigue at rest) in 28.6 % and as fatigability (fatigue with exercise) in the rest of the patients. In 64.3 % of the patients, fatigue produced limited activity at work and in social activity. There was no significant correlation between the fatigue descriptive scale or disease related parameters, including duration of disease and disability. However, Hamilton depression scale scores were higher in patients with fatigue and significantly correlated with fatigue descriptive scores (p = 0.007, r = 0.56). Conclusion: It could be concluded that fatigue is independent of physical disability and significantly correlated to depression. The association of depression and fatigue could be explained by brain lesions in specific neuroanatomic pathways or psychological factors. Further studies are needed to clarify the effect of antidepressant medication on multiple sclerosis fatigue.
Keywords: Depression; Fatigue; Multiple sclerosis; Physical disability